Prenatal massage is effective in reducing back pain in Third trimester pregnant women - Handayani, Dewi (Universitas 'Aisyiyah Yogyakarta, 2023)
Pregnancy is a physiological process, which causes changes in adaptation to body systems including the musculoskeletal system. The discomfort that occurs due to these changes is back pain. The purpose of the study was to determine the effectiveness of prenatal massage therapy on reducing back pain for third trimester pregnant women in the working area of the Bineh Krueng Aceh Health Center in 2023. Quasi-Experimental type of research, with One Group Pre Test—Posttest design. The population of this study was 3rd Trimester Pregnant Women from December 2022 to February 2023, which was 53 people with a total sample of 15 3rd trimester pregnant women taken using purposive sampling techniques. The research instrument used was a Numerical Rating Scale (NRS) pain scale observation sheet to measure pain levels before and after prenatal massage therapy intervention. Data analysis with univariate and bivariate with Wilcoxon test. The average back pain before prenatal massage was 1.73 with an SD value of 0.704 and the average after prenatal massage was 0.53 with an SD value of 0.640. It can be concluded that there is an effectiveness of prenatal massage therapy on reducing back pain for third trimester pregnant women in the Bineh Krueng Health Center Work area in 2023 with Wilcoxon test results value p = 0.001 (p value < α).